2013
DOI: 10.2166/aqua.2013.026
|View full text |Cite
|
Sign up to set email alerts
|

Failure mechanisms and condition assessment of PVC push-fit joints in drinking water networks

Abstract: This paper presents and discusses the significant role played by joints in the failures registered in drinking water distribution networks. The three most important failure mechanisms related are presented and a procedure to detect them through the visual measurement of the gap between pipes inside a joint is proposed. The procedure is proved to be a valuable source of information on joint condition after the assessment of a 600-m DN500 PVC pipe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Kirby (1981) reported that over insertion and angularity of the pipe accounts for 12.4% of all failures in PVC push fit joints. Arsénio et al, (2013) established that disconnection through joint rotation and axial pull out were the most important failure mechanisms for push fit joints (flexible joint) in PVC pipes. This is typically found where the angle of the pipe join increases past 10 o requiring a reduction in joint depth.…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…Kirby (1981) reported that over insertion and angularity of the pipe accounts for 12.4% of all failures in PVC push fit joints. Arsénio et al, (2013) established that disconnection through joint rotation and axial pull out were the most important failure mechanisms for push fit joints (flexible joint) in PVC pipes. This is typically found where the angle of the pipe join increases past 10 o requiring a reduction in joint depth.…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…However, we can distinguish the following causes of failures [7,8,9,10,11,12]:  design errors, mechanical or material defects,  internal or external corrosion,  operational errors,  bursting with overload,  transverse or longitudinal cracks,  fractures,  other or unknown causes. Failures can also be caused by:  earth moves or other natural hazards [13],  external impact or other random events [14],  errors in connection [15]. The formation of failure requires analysing several reasons, it is related to errors in the design, construction and operation of water supply network [12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that internal pressure from increased water demand during the summer months may be the reason for PVC pipe failures 8 . This is reported as particularly detrimental in push-fit joints since they do not provide restraint from thrust from internal pressure forces, resulting in axial pull out or disconnection 26,27 . In these data we did not have access to either pressure data or failure type, therefore further investigation is required to support the literature in this area and understand the main failure mechanism.…”
Section: Polyvinyl Chloridementioning
confidence: 99%